MAPPING THE HAPPINESS LEVEL DISPARITY OF THE INDONESIAN POPULATION USING MULTIDIMENSIONAL SCALING - Sumin, Sumin; Retnawati, Heri (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The Central Statistics Agency has published a survey report on the happiness of the Indonesian people in 2017. The survey results show that there are disparities that vary between provinces. The province with the highest happiness index was North Maluku, while the province with the lowest happiness index was Papua. Based on this phenomenon, the researcher wants to map the provinces based on the similarity of happiness levels. Researchers used quantitative descriptive methods with data analysis using multidimensional scaling. The results show that the provinces that have similarities with the happiest group are: [1] North Maluku province is like Riau Islands, Gorontalo, North Sulawesi, and Maluku. [2] South Kalimantan is like North Kalimantan, East Kalimantan, DI Yogyakarta, and Bali. [3] DKI Jakarta is like West Papua. [4] South Sulawesi is like West Sumatra, Riau, and South Sumatra. [5] Aceh is like Kep. Bangka Belitung. The less happy group [1] West Java is like Banten, Central Java, Central Kalimantan, Jambi, and East Java. [2] North Sumatra is like Papua. [3] Central Sulawesi is like Southeast Sulawesi, West Nusa Tenggara, Bengkulu, West Kalimantan, West Sulawesi, Lampung, and East Nusa Tenggara.